Geopolitical reasons for the break-up of Tito’s Yugoslavia in the context of the international hegemony of the USA - Despotovic, Ljubiša; Glišin , Vanja (Napredak, 2021)
We will present the main geopolitical reasons for the creation of the Kingdom of the SCS-Yugoslavia and follow their effect until the moment those reasons led to the decision of the Neo-Atlanticists to liquidate Broz’s SFR Yugoslavia as a state and geopolitical project of the Entente forces. The process of the disintegration of the SFRY proceeded quickly and decisively with the imposition of new geopolitical interests of Neo-Atlanticism and foreign policy priorities. At that time, a new hegemon in the monopolar political order emerged, following the downfall of bipolarism that had dominated the world stage for more than four decades. All the geopolitical transgressions of the USA, both in the zones of the post-Soviet order of power and in the territorial area of the post-Yugoslav geopolitical experiment, produced a mutilation of the statehood, demography, territory, identity, language, culture and economy of Serbs in the area.
Keywords: Geopolitics; SFR Yugoslavia; Neo-Atlanticism; Serbs; Contemporary International Relations; Hegemony